Paham Ketuhanan Uis Neno, Uis Pala, dan Bei Nai dalam Ritual Oe Kana di Suku Dawan, Nusa Tenggara Timur - Adrianus Musu Sili (STP St. Bonaventura Medan, 2024)
Abstract This study aims to examine the concept of divinity in the Dawan tribe through the Oe Kana ritual. There are two known concepts of divinity, namely Uis Neno and Uis Pala. In addition, the Dawan tribe also has the figure of Bei Nai as an ancestral spirit. These three figures are the main focus of this research. This research uses quantitative analysis of scholarly sources related to the theme of the writing. In this research, Arnold van Gennep's study is applied with three approaches: pre-liminal, liminal, and post-liminal, to understand the Oe Kana ritual. The results show that the Dawan tribe honours Uis Neno and Uis Pala as life givers in their daily lives. Keywords: Oe kana, Uis Neno, Uis Pala, Bei Nai, Arnold van Gennep.